''Phenomenal mind" and "conceptual mind" paradigms in psychology: ¿Is unity possible? - Dávila Dávila, Alex (2004)
This year, psychology reaches as a discipline 125 years since the beginning of activities at the first experimental laboratory in Leipzig. Through this long period, psychology has evolved as a complex discipline in which severa! epistemological visions have grown accompanying the expansion of the field. We propase to analyze this process by applying the concepts of phenomenal mind and conceptual mind on severa! psychological approaches, including main historical and contemporary "schools". Analysis suggests the existence of complex relations and mutual influences among psychologies, uneasiness to classify sharply al! psychologies as phenomenal or conceptual, and the potential to unify psychology as a science by including phenomenological points of view in contemporary psychology.